2007
DOI: 10.1016/j.cell.2007.02.048
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionarily Conserved Mechanism for MicroRNA-223 Expression Revealed by MicroRNA Gene Profiling

Abstract: Many microRNAs (miRNAs) are evolutionarily conserved and have intriguing expression patterns. Tissue and/or time-specific expressions of some miRNAs are presumably controlled by unique cis-acting regulatory elements that coevolved with the miRNA sequences. Exploiting bioinformatics, we identified several miRNAs whose primary transcripts could be regulated by conserved genomic elements proximal to their transcription start sites. Such miRNAs include microRNA-223 (miR-223), which is reportedly controlled by a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
257
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(271 citation statements)
references
References 38 publications
12
257
0
Order By: Relevance
“…Given that NFIA is in itself a target of miR-223, an auto-regulatory loop can be conceived. An alternative regulatory mechanism for this process has also been delineated by Fukao et al 36 These investigators found a PU.1 and C/EBPb-binding site capable of activating miR-223 transcription in mice. The PU.1-binding site is conserved in humans, making this a strong candidate for the control of miR-223 expression.…”
Section: Myeloid Developmentmentioning
confidence: 97%
“…Given that NFIA is in itself a target of miR-223, an auto-regulatory loop can be conceived. An alternative regulatory mechanism for this process has also been delineated by Fukao et al 36 These investigators found a PU.1 and C/EBPb-binding site capable of activating miR-223 transcription in mice. The PU.1-binding site is conserved in humans, making this a strong candidate for the control of miR-223 expression.…”
Section: Myeloid Developmentmentioning
confidence: 97%
“…In the same study, miR-223 was shown to target Nfia, an osteoclastogenesis suppressor that eventually negatively regulates the M-CSF receptor. Later, other groups validated these effects of miR-223 on osteoclastogenesis and revealed PU.1-binding sites in the miR-223 promoter (Fukao et al 2007, Sugatani & Hruska 2009, Shibuya et al 2013. Sugatani et al posited the existence of a feed-forward network whereby M-CSF induces PU.1 in osteoclast precursors, and PU.1 stimulates pri-miR-223 transcription, which, by downregulating the expression of Nfia, ultimately increases the levels of M-CSF receptor.…”
Section: Mirnas and Osteoclast Differentiationmentioning
confidence: 99%
“…Although miR-223 was initially reported to be restricted to myeloid cells (14), multiple groups have since demonstrated functional miR-223 expression in nonmyeloid cell types, including hepatocytes (15). Hepatic miR-223 levels were found to be significantly increased upon ischemic/reperfusion injury (16) and decreased in hepatocellular carcinoma (17).…”
mentioning
confidence: 99%